PERSPECTIVE OF CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOMEN (CEDAW) ON THE CYBER HARASSMENT IN INDONESIA - Gunawan, Yordan; Sardi, Martinus; khairunnisa, Khairunnisa (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
In 2017, there are 3,528 cases of violence against women in Indonesia, in which 76% of violence occurs in the form of sexual harassment. Sexual harassment is a part of discrimination against women, therefore the United Nations issued the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) as a safeguard of women’s rights. Nowdays, sexual harassment has developed into a new form, namely cyber harassment. Unfortunately, in CEDAW, there is no clear and specific statement related to it. This study is a normative legal research with Statute Approach and Case Approach. By using the qualitative descriptive method, this study will elaborate on the protection of women from cyber harassment in Indonesia based on the perspective of CEDAW. The result shows that, as the international treaty, CEDAW does not provide any punishment for the suspect to be prosecuted. Fortunately, Indonesia has Law No. 11 of 2008 on Electronic Information and Transactions to deal with cyber harassment cases. The author recommends the Indonesian government to formulate a new law dealing with cyber harassment. Aside of that, education to the society on cyber harassment itself needs to be conducted by the government to prevent more victims in the future.